2017
DOI: 10.5858/arpa.2016-0494-oa
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Analysis of Discordant Diagnoses in Digital Pathology Compared With Light Microscopy

Abstract: Context.-Relatively little is known about the significance and potential impact of glass-digital discordances, and this is likely to be of importance when considering digital pathology adoption.Objective.-To apply evidence-based medicine to collect and analyze reported instances of glass-digital discordance from the whole slide imaging validation literature.Design.-We used our prior systematic review protocol to identify studies assessing the concordance of light microscopy and whole slide imaging between 1999… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 33 publications
3
70
0
2
Order By: Relevance
“…Moreover, reanalysis of the discordances showed that only two (minor and major) discrepancies could be attributed to the use of digital pathology (2%), while the other eight discrepancies were due most probably to differences in awareness and interpretation by the individual pathologists. This high overall concordance rate is within the range of previously observed inter‐ and intraobserver variability in digital and microscopic pathology in general, and is in line with previous single‐institute studies by our group and others …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, reanalysis of the discordances showed that only two (minor and major) discrepancies could be attributed to the use of digital pathology (2%), while the other eight discrepancies were due most probably to differences in awareness and interpretation by the individual pathologists. This high overall concordance rate is within the range of previously observed inter‐ and intraobserver variability in digital and microscopic pathology in general, and is in line with previous single‐institute studies by our group and others …”
Section: Discussionsupporting
confidence: 91%
“…This high overall concordance rate is within the range of previously observed inter-and intraobserver variability in digital and microscopic pathology in general, and is in line with previous single-institute studies by our group 7-10 and others. 11,12 Although there have been many studies validating digital diagnostics, only a few studies validate remote diagnostics specifically. Furness et al evaluated the adequacy of WSI as a medium for internet-based telepathology in the context of the National Renal Pathology External Quality Assurance scheme in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 45 pathology laboratories in The Netherlands, 16 own a digital slide scanner, including the eight academic pathology laboratories, and many more have serious plans to buy hardware. However, the adoption of digital pathology for primary diagnostics has remained relatively low, despite widespread validation of digital pathology for primary diagnostics …”
Section: Introductionmentioning
confidence: 99%
“…However, the adoption of digital pathology for primary diagnostics has remained relatively low, despite widespread validation of digital pathology for primary diagnostics. 12,13 The University Medical Centre (UMC) Utrecht committed 10 years ago to building up a digital pathology infrastructure based on three Aperio scanners (Leica Biosystems, Wetzlar, Germany), a tape storage system, and custom in-house-developed image integration software, amassing a complete digital archive of scanned histology slides over the last 10 years. 1 As of the end of 2015, the total amount of digital slides scanned and archived in the UMC Utrecht digital slide archive (including slides scanned for research) was in the order of 500 terabytes, with >1 200 000 million scanned slides being archived.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic analysis of instances of diagnostic discordance in glass–digital comparisons of the same histology cases found 335 instances of diagnostic discordance out of 8069 documented instances of a glass diagnosis being compared with a digital diagnosis (4%) 10 . The majority of these discordances would have had no clinical significance, and reflected diagnostic scenarios prone to intra‐ and interobserver variation in diagnosis, regardless of the diagnostic medium used.…”
Section: Literature Reviewmentioning
confidence: 99%